The forest pedagogy programs in Croatia – evaluation approach and findings (Journal of Forestry, 2025)
Forest pedagogy (FP), an educational concept that utilizes the forest as a natural classroom, is gaining recognition in Croatia. The establishment of the Silva.Rei Center for Forest Pedagogy in 2022 marked a significant step in the development of forest pedagogy and its associated educational approach in the country. This paper aims to present evaluation findings from two FP  programs conducted by the Center within the "Znanje iz šume za šumu" project.The evaluation encompasses two distinct FP programs: field workshops for elementary school students and a seminar for educational staff. The assessment focused on participant satisfaction, the usefulness and practical applicability of the content for educators, the level of knowledge acquired, and the most engaging elements of the workshops for students. Evaluation results indicate high levels of engagement and motivation among participants, underscoring the social and ecological benefits of FP, along with recommendations for future program improvements.Key findings from the evaluation of the field workshops include the following: 97.3% of participants reported that engaging in activities such as tracking animal signs and counting sounds was the most enjoyable aspect. This finding suggests that students particularly enjoyed practical tasks involving physical engagement and sensory exploration. These activities allowed students to actively participate and use their senses, resulting in a high level of engagement and satisfaction.89.19% of participants highlighted that socializing with friends in the forest environment was one of the best aspects of the workshop. The high percentage of students who emphasized social interaction underscores the importance of the social dimension in outdoor learning and exploration. The forest setting fostered relaxed and natural interactions, contributing to positive experiences and the formation of friendships among children.All the FP conference participants (100%) rated the presentations as interesting and comprehensible. Additionally, 100% confirmed that the topics presented were perceived as practically applicable. This result indicates a high relevance and usefulness of the topics covered for seminar participants. The findings reveal that the structure and content of the seminar, along with the presenters, were perceived as notably effective, with a significant proportion of participants expressing high satisfaction with the presentations and field demonstrations. Furthermore, most participants indicated a willingness to pursue further training in the field of forest pedagogy.For the evaluation of the FP field workshops included 37 students from mixed lower grades. An anonymous questionnaire assessed participant satisfaction and the level of content learned during the workshop, indicating a high level of engagement and enjoyment among students.Similarly, the forest pedagogy conference held at the Faculty of Forestry and Wood Technology in Zagreb, involved 30 educators, including four students. The evaluation revealed that all participants found the presentations engaging and comprehensible, with unanimous agreement on the practical applicability of the topics. Recommendations for future seminars include focusing on fewer topics with more depth and incorporating more concrete examples.In conclusion, forest pedagogy has proven to be an effective educational approach that imparts knowledge about nature while fostering social skills and environmental awareness among children. Regular evaluations during the program's duration are essential for ensuring the program remains dynamic and relevant.